2014
DOI: 10.1128/aem.02423-14
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Organized Films from Bdellovibrio bacteriovorus Prey Lysates

Abstract: Bdellovibrio bacteriovorus is a Gram-negative predator of other Gram-negative bacteria. Interestingly, Bdellovibrio bacteriovorus 109J cells grown in coculture with Escherichia coli ML-35 prey develop into a spatially organized two-dimensional film when located on a nutrient-rich surface. From deposition of 10 l of a routine cleared coculture of B. bacteriovorus and E. coli cells, the cells multiply into a macroscopic community and segregate into an inner, yellow circular region and an outer, off-white region.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…As such, the addition of prey or lowering of nutrient accessibility results in phenotypic changes and detachment of the biofilm (Medina and Kadouri, 2009). A similar phenomenon was described by Ferguson et al (2014), with B. bacteriovorus forming spatially organized communities of differentiated bacteria, with a central core of predatory active bacteria, and an outer morphologically heterogeneous community of HI cells. The presence of nutrient and lack of access to prey favored the diversification, and it was speculated that this phenotypic change resembling a biofilm may benefit BALOs persistence in the environment.…”
Section: Balos Self-formation Of Biofilmssupporting
confidence: 53%
“…As such, the addition of prey or lowering of nutrient accessibility results in phenotypic changes and detachment of the biofilm (Medina and Kadouri, 2009). A similar phenomenon was described by Ferguson et al (2014), with B. bacteriovorus forming spatially organized communities of differentiated bacteria, with a central core of predatory active bacteria, and an outer morphologically heterogeneous community of HI cells. The presence of nutrient and lack of access to prey favored the diversification, and it was speculated that this phenotypic change resembling a biofilm may benefit BALOs persistence in the environment.…”
Section: Balos Self-formation Of Biofilmssupporting
confidence: 53%
“…It is also worthy to mention that the hit locus and its nearby pilus genes (Bd0108~Bd0119) were downregulated by approximately 2~3fold (Table S3, worksheet 4). Given the importance of this locus for predation [30,31] and its high expression level in the attack phase compared to the intraperiplasmic phase [9,32], this might partially explain why B. bacteriovorus predation is less efficient in rich media as previously found by other groups [33,34]. In Rotem et al, it was found that incubating planktonic AP predatory cells with ghost prey cells together with either PYE medium or prey extract led to the silencing of the hit locus (Bd0108) and that was attributed mainly to the presence of the ghost prey cells [10].…”
Section: Discussionmentioning
confidence: 77%
“…In short, a culture of B. bacteriovorus 109J exponentially growing on P. fluorescens LP6a was harvested, centrifuged at 1000 g for 10 min, filtered through a 0.45 μm pore-size Millex filter and re-suspended in HEPES metals (HM) buffer (Ferguson et al, 2014). About 0.3 ml of this suspension was placed in a small chamber formed by a U-shaped capillary placed on a microscope slide and closed with a glass coverslip in order to prevent the formation of air bubbles within the chamber.…”
Section: Dispersal Experimentsmentioning
confidence: 99%